THE EFFECT OF TRANSFORMATIONAL LEADERSHIP STYLE, WORK MOTIVATION AND DISCIPLINE ON EMPLOYEE PERFORMANCE - Anah, Sri; Widayati, C. Catur; W., Anggi (Dinasti Publisher, 2020)
The purpose of this research is to know and analyze the influence of transformational leadership style, work motivation and discipline to employee performance at PT Berkah Makmur. This research is a kind of causal associative research which is obligatory for relationship relation between one variable with other variable or the like. The population in this study are employees who work in PT Berkah Makmur. Sampling method using saturated sampling technique with the number of samples of 32 respondents. Primary data were collected through questionnaires, secondary data. Data analysis method used is descriptive and quantitative analysis method with multiple linier regression analysis technique. The result of hypothesis test show that transformational leadership style and work motivation have no effect on employee performance in Koperasi Berkah Makmur, but discipline to employee performance in Koperasi Berkah Makmu. Determination coefficient test shows 813% employee performance can be explained by the variables of transformational leadership style, work motivation, and discipline, while the remaining 18.7% is explained by other factors not included in this study